Pengaruh Penggunaan Media Pembelajaran Biologi Berbasis Mobile Learning terhadap Minat dan Kemampuan Berpikir Kreatif Siswa SMA Kota Masohi: Effect of the used of Biology Learning Media Based on Mobile Learning on Learning Interest and Creative Thinking Ability of High School Students in Masohi City - Calvin Talakua; Sovian Sesca Elly (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
Biology Learning Media Based on Mobile Learning is important to be developed to fulfill student’s need in industrial revolution 4.0. This study aims to determine the effect of using Biology Learning Media Based on Mobile Learning on high school students' learning interest and the creative thinking ability in Masohi City. This research is a quasi experiment with the design of Pretest-Posttest Non-Equivalent Control Group. The samples are SMA Negeri 1 Masohi and SMA Negeri 2 Masohi. The result of this study shows that there is an effect of the use of Biology Learning Media Based on Mobile Learning on learning interest and creative thinking abilities of high school students in Masohi City. Related to the results of this study, it is recommended for high school biology teachers in Masohi City to use Biology Learning Media Based on Mobile Learning in class because it gives meaningful practical experience so that students' interest in learning and creative thinking skills can be improved. Keywords: Biology Learning Media Based on Mobile Learning, Learning Interest, Creative Thinking Ability. Abstrak: Media pembelajaran biologi berbasis mobile learning penting dikembangkan untuk memenuhi kebutuhan siswa seiring perkembangan revolusi industri 4.0. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan media pembelajaran biologi berbasis Mobile Learning terhadap minat belajar dan kemampuan berpikir kreatif siswa SMA di Kota Masohi. Penelitian ini termasuk quasi eksperiment dengan rancangan Pretest-Postest Non-Equivalent Control Group. Sampel penelitian adalah SMA Negeri 1 Masohi dan SMA Negeri 2 Masohi. Hasil penelitian menunjukkan bahwa ada pengaruh penggunaan media pembelajaran berbasis Mobile Learning terhadap minat belajar dan kemampuan berpikir kreatif siswa SMA di Kota Masohi. Terkait dengan hasil penelitian ini, maka disarankan untuk guru-guru biologi SMA di Kota Masohi agar lebih sering menggunakan media pembelajaran berbasis Mobile Learning dalam pembelajaran di kelas karena melalui pembelajaran tersebut siswa memperoleh pengalaman praktek yang berarti (meaningful) sehingga minat belajar dan kemampuan berpikir kreatif siswa dapat ditingkatkan. Kata kunci: Media Pembelajaran Biologi Berbasis Mobile Learning, Minat Belajar, Kemampuan Berpikir Kreatif.